Pequeño Mapache pesca un resfriado - Canizares, Susan, 1960-; Denise, Christopher (New York : Scholastic, 2002)
Little Raccoon packs his baseball mitt, butterfly net, and water pail, and with his pal Red Squirrel in tow, goes out to catch a cold.
Keywords: Procyon -- Juvenile fiction; Cold (Disease) -- Juvenile fiction; Sick -- Juvenile fiction; Spanish language materials